PENGARUH PERATAAN LABA MELALUI MANIPULASI AKTIVITAS RIIL TERHADAP PERSISTENSI LABA - Nining Ika Wahyuni (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
This research aims to provide empirical evidence concerning the effect of income smoothing through real activities manipulation to the earning persistence. By using quarterly financial statement, this study also supposes to determine the timing of smoothing taken by the suspect firm. This study investigates three types of real activity manipulation: abnormal cash flow operation, abnormal discretionary expense, and abnormal production cost. Real earning manipulation is measured by summing the standardized of the three proxies. Companies that have been used as a sample in according to the purposive sampling criteria’s are consist of 63 firms on five years observations (2011-2015). From this number, samples included into income smoothing criteria based on Eckel Model are consist of 26 firms. The first hypothesis was tested with regression analisys and the second was tested with independent sample t-test. The first hypothesis test result showed that income smoothing via real earning manipulation negatively affect the earning persistence. But, the statistic test of the second hypothesis show that mean difference between earning persistence in the fourth fiscal quarter and in the other quarters was statistically insignificant. Thus, we can conclude that there is no difference between earning persistence in the fourth fiscal quarter and other quarters.